Dukungan Filipina Terhadap Teknologi 5G Huawei di Tengah Tekanan Politik Amerika Serikat - Mastaridevi, Luh Putu; Wiranata, I Made Anom; Parameswari, A. A Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This research aims to describe the reason behind the Government of Philippine supporting 5G technology from Huawei through qualitative method. Massive pressure from United States as alliance who bans Huawei and spread the message to all states over the world does not influence Philippine from using this technology nationally. Eventhough United States has spesifically warned Philippine to avoid using 5G from Huawei in a state visit, Philippine keep taking different decision and support this technology. Therefore, Reseacher uses three main concepts such as Neoclassical Realism, Cybersecurity, and Digital Economy to answer the reason behind Philippine support towards Huawei’s 5G. This research appraises that Philippine’s support as a response to international structure and domestic factor which put digital economy and cybersecutiy forward through the implementation of Huawei’s 5G.   Keywords: Phillipine, 5G, Huawei, Neoclassical Realism